2007
DOI: 10.1001/archpedi.161.6.539
|View full text |Cite
|
Sign up to set email alerts
|

Dating Violence, Sexual Assault, and Suicide Attempts Among Urban Teenagers

Abstract: In this population of urban youth, recent dating violence among females and lifetime history of sexual assault among males were significantly associated with suicide attempts. Clinicians and educators should be trained to routinely screen adolescents for violence victimization and should have a low threshold for referring these at-risk teenagers for mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 40 publications
8
103
0
4
Order By: Relevance
“…Seksuelle overgrep kan føre til en rekke negative ettervirkninger i form av psykiske og somatiske problemer (2)(3)(4)(5).…”
Section: > Se Også Side 1907unclassified
See 1 more Smart Citation
“…Seksuelle overgrep kan føre til en rekke negative ettervirkninger i form av psykiske og somatiske problemer (2)(3)(4)(5).…”
Section: > Se Også Side 1907unclassified
“…Seksuelle overgrep er assosiert med en rekke helseproblemer, deriblant smerte, angst, depresjon, svimmelhet, hjertebank, søvnløshet, trøtthet og energiløshet, forstoppelse og diaré (3,4). En stor, retrospektiv kohortstudie viste at seksuelle overgrep i barneog ungdomsårene var assosiert med alkoholproblemer, bruk av illegale narkotiske stoffer, selvmordsforsøk og ekteskaps-og familieproblemer i voksen alder hos både kvinner og menn (7).…”
Section: > Se Også Side 1907unclassified
“…89 A recent large study of New York City students found that nearly 10% of girls and more than 5% of boys reported a lifetime history of being sexually assaulted, and 10% of both boys and girls reported experiencing dating violence in the previous year. 90 Although exposure to media violence is not the sole factor contributing to aggression, antisocial attitudes, and violence among children and adolescents, it is an important health risk factor on which we, as pediatricians and members of a compassionate society, can intervene. Some research has suggested that interventions of the types discussed below can reduce mediaviolence consumption and its effects on children and adolescents.…”
Section: Aap Actionmentioning
confidence: 99%
“…Dating violence is another risk factor of suicide attempts. Those who had been hit by a girlfriend or boyfriend were twice as likely to report attempted suicide (Epstein & Spirito, 2009;Olshen, McVeigh, Wunsch-Hitzig, & Rickert, 2007).…”
Section: Introductionmentioning
confidence: 99%